2015
DOI: 10.1051/0004-6361/201525688
|View full text |Cite
|
Sign up to set email alerts
|

Angular momentum transport and large eddy simulations in magnetorotational turbulence: the small Pm limit

Abstract: Context. Angular momentum transport in accretion discs is often believed to be due to magnetohydrodynamic turbulence mediated by the magnetorotational instability (MRI). Despite an abundant literature on the MRI, the parameters governing the saturation amplitude of the turbulence are poorly understood and the existence of an asymptotic behaviour in the Ohmic diffusion regime has not been clearly established. Aims. We investigate the properties of the turbulent state in the small magnetic Prandtl number limit. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 63 publications
4
55
0
Order By: Relevance
“…The ratio of Maxwell to Reynolds stresses is solely determined by Rm and increases from 0 to 1 as Rm is increased. This is in agreement with Meheut et al (2015), who performed shearing-box simulations of MRI turbulence at two magnetic Reynolds numbers Rm = 400 and 2600, while varying either Pm. At each Rm they found a constant, but different, ratio of Maxwell to Reynolds stress for both azimuthal and axial magnetic fields, with Maxwell stresses growing with Rm.…”
Section: Discussionsupporting
confidence: 91%
“…The ratio of Maxwell to Reynolds stresses is solely determined by Rm and increases from 0 to 1 as Rm is increased. This is in agreement with Meheut et al (2015), who performed shearing-box simulations of MRI turbulence at two magnetic Reynolds numbers Rm = 400 and 2600, while varying either Pm. At each Rm they found a constant, but different, ratio of Maxwell to Reynolds stress for both azimuthal and axial magnetic fields, with Maxwell stresses growing with Rm.…”
Section: Discussionsupporting
confidence: 91%
“…Numerical simulations of visco-turbulent discs exhibit values of α ∼ 10 −3 − 10 −2 (e.g. Meheut et al 2015). Dust grains are assumed to be compact, spherical, uncharged, of constant size and density.…”
Section: Hypothesismentioning
confidence: 99%
“…It is also about twice larger than the mean field B0y = 0.1 (Table 1). turbulence in disks with a net azimuthal field (Hawley et al 1995;Guan et al 2009;Meheut et al 2015). For all the models, the time-and volume-averaged quantities over the whole quasi-steady state, between t = 100 and the end of the run at t f , are listed in Table 1.…”
Section: Simulations and General Characteristicsmentioning
confidence: 99%
“…Fleming et al (2000) in local model and Flock et al (2012b) in global model addressed the influence of resistivity and established a critical value of magnetic Reynolds number for the existence of turbulence. and Meheut et al (2015) included also viscosity together with resistivity and showed that at fixed field strength the saturation amplitude mainly depends on the magnetic Prandtl number, that is, the ratio of viscosity to resistivity, if the latter is larger than unity and the Reynolds number is high enough. On the other hand, at Prandtl numbers smaller than unity the turbulence sustenance is more delicate: it appears to be independent of the Prandtl number and mainly determined by the magnetic Reynolds number.…”
Section: Introductionmentioning
confidence: 99%